When Your Mouth Says Yes and Your Body Says No: Understanding Body Language in Mediations and Negotiations - Ciraco, Danny (UnderCurrents: Journal of Critical Environmental Studies, 1999)
Before language, before writing, before any formalized communication process, there was, and continues to be, nonverbal communication. [...]